DUPLICATE RELATIONS IN THE TERMINOLOGY SYSTEM - Ixtiyor Ermatov (Western European Studies, 2025)
The word is the basic unit of language. It is impossible to imagine a language without speech sounds, grammatical forms and outside the communication process. The system of speech sounds, the complex of morphological forms and the devices serving for communication - all together constitute the language, its whole organism. All this is formed with the help of words. One of the functional-semantic manifestations of the word is the term. The “partial similarity” of words and terms to the content aspect of the language is that, while the content aspect of words, as mentioned above, includes meanings that are jointly formalized in the memory of the whole people, the content aspect of terms includes concepts that are jointly formalized in the memory of certain groups of individuals specializing in a particular science, technology and profession. Concept and meaning, although they are considered common phenomena related to the content aspect of language, differ from each other: the “practical scope” of the concept is wider than the “practical scope” of meaning, since meaning is an ideal unit included in the scope of the concept. This article studies the functional-semantic features of the Uzbek intralinguistic (immanent) linguistics terminological system related to the content plan, and is devoted to the terminological systems of modern areas of lexicology and the issues of doublets in terminology. Linguistic terms serve as illustrative material for the article
Keywords: language; word